2015
DOI: 10.1002/clc.22485
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Short‐term Blood Pressure Variability in Patients With Ascending Aortic Dilatation

Abstract: Background: Blood pressure variability (BPV) is a novel parameter related to adverse cardiovascular findings and events, especially in hypertensive patients. The aim of the present study was to investigate the relationship between short-term BPV and ascending aortic dilatation (AAD). Hypothesis: Hypertensive patients with AAD may exhibit higher short-term BPV compared to hypertensive patients with normal diameter ascending aorta and BPV may be correlated with aortic sizes. Methods: Seventy-six hypertensive pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 31 publications
(37 reference statements)
1
1
0
Order By: Relevance
“…In the current study, based on our multicenter data, we found that patients with a history of hypertension were more likely to have high SBPV, which was further associated with an increased incidence of AEs. These findings could be explained by the abnormal BP rhythm and poor BP control and were in line with the results of previous studies (17,19,33). There is a challenge, however, in estimating the average SBPV and classifying the patients into high and low SBPV groups given different target populations in clinical practice; additionally, when using only the SD of the SBP as a summary measure, there is a loss of information.…”
Section: The Review In the Context Of Other Literaturesupporting
confidence: 89%
“…In the current study, based on our multicenter data, we found that patients with a history of hypertension were more likely to have high SBPV, which was further associated with an increased incidence of AEs. These findings could be explained by the abnormal BP rhythm and poor BP control and were in line with the results of previous studies (17,19,33). There is a challenge, however, in estimating the average SBPV and classifying the patients into high and low SBPV groups given different target populations in clinical practice; additionally, when using only the SD of the SBP as a summary measure, there is a loss of information.…”
Section: The Review In the Context Of Other Literaturesupporting
confidence: 89%
“…The PAMELA study (Pressioni Arteriose Monitorate E Loro Associazioni) assessed home blood pressure monitoring (HBPM) and 24-h ambulatory blood pressure monitoring (ABPM) results in 1860 participants and concluded that BP was significantly correlated with ARD ( r = 0.35 for home SBP, r = 0.24 for 24-h SBP, P < 0.01 for both) [25]. Another two studies found that hypertensive patients with ascending aortic dilation had higher short-term blood pressure variability (BPV, assessed by standard deviation and coefficient of variation of BP) than those without dilation, indicating short-term BPV assessed by 24-h ABPM was a remarkable risk factor for aortic dilation in hypertensive patients [43,44]. Moreover, cumulative SBP load takes account of both magnitude and duration of exposure to elevated BP and has been confirmed as a promising predictor of cardiovascular risk [45].…”
Section: Proximal Aorta Dilatation and Hypertensionmentioning
confidence: 99%